Automated fuel quality detection and dispenser control system and method, particularly for aviation fueling applications - KASTNER CHRISTOPHER K; JENSEN KEVIN G; WETMORE PHILLIP A (2015)
A fuel quality monitoring system and method to automatically and/or continuously monitor quality of fuel dispensed and control the operation of the fuel dispenser. The control system monitors fuel quality to prevent unsafe refuelings when the fuel quality is unacceptable. In one embodiment, a combination of a differential pressure sensor and a fuel quality monitoring device. If fuel quality is at an acceptable level although not ideal, the control system can allow fueling with the generation of reports and alarms. If the fuel quality is unacceptable, fuel flow can be stopped. If the differential pressure across the filter indicates a high degree of debris and/or water retention, the control system can automatically lower the flow rate to reduce the risk of filter breakdown without completely preventing fueling until the filter can be replaced.